2016
DOI: 10.11599/germs.2016.1095
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus gastroenteritis in children less than five years of age in primary care settings in Bulgaria: an observational study

Abstract: NCT01733849.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…A scoring manual prepared for use of the Vesikari scale in clinical trials presupposes parent completion of daily diary cards and stringent control by specially trained study clinicians 23 but adoption of such a strict protocol was not considered necessary for this study. The same informal severity scoring approach was used in the companion study in Bulgaria 12 and we have no obvious explanation for the striking difference in the average severity scores observed in the two studies. As mentioned in the introduction, Latvia included fully reimbursed vaccination in the NIP in 2015.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A scoring manual prepared for use of the Vesikari scale in clinical trials presupposes parent completion of daily diary cards and stringent control by specially trained study clinicians 23 but adoption of such a strict protocol was not considered necessary for this study. The same informal severity scoring approach was used in the companion study in Bulgaria 12 and we have no obvious explanation for the striking difference in the average severity scores observed in the two studies. As mentioned in the introduction, Latvia included fully reimbursed vaccination in the NIP in 2015.…”
Section: Discussionmentioning
confidence: 83%
“…A companion study based on the same protocol was performed in Bulgaria with data collection during the calendar year 2013. 12 The overall proportion of RV-positive cases was 25.5% in Bulgaria compared with 38.1% in Latvia but both studies found that the proportion of RV-positive cases increased linearly with age and more than doubled for children aged 24-59 months compared to the youngest infants aged 0-5 months. The severity assessments were very different in the two studies.…”
Section: Discussionmentioning
confidence: 90%